BRCA1-associated and sporadic ovarian carcinomas: outcomes of primary cytoreductive surgery or neoadjuvant chemotherapy. Issue 4 (5th March 2019) - Gorodnova, Tatyana; Sokolenko, Anna; Ni, Valeria; Ivantsov, Alexandr; Kotiv, Khristina; Petrik, Sergey; Amelina, Inna; Berlev, Igor; Imyanitov, Evgeny
Abstract : Objective: Tumors arising in BRCA1/2 mutation carriers are characterized by increased platinum sensitivity; however, it is unknown whether this feature should be considered while choosing between primary surgical versus systemic treatment. This study aimed to compare outcomes of ovarian cancer patients undergoing either primary surgery or interval cytoreduction based on BRCA1/2 status. Methods: The study included consecutive ovarian cancer patients, who were treated at the N.N. Petrov Institute of Oncology (St Petersburg, Russia) from 2000 to 2013 and who underwent complete or optimal cytoreductive surgery. A comparison of disease outcomes was performed for the total group of ovarian cancer patients as well as for 69 BRCA1 -mutated and 151 sporadic high-grade serous advanced-stage ovarian carcinomas. Frequency comparisons were performed by Chi-square test or Fisher exact test. Disease-free interval and overall survival were analyzed by Mann-Whitney U-test and Kaplan-Meier method. Hazard ratios were calculated by Cox regression analysis. Results: The analysis included 283 consecutive patients who underwent optimal cytoreduction (size of residual tumor <1 cm (n=156)) or complete tumor excision (n=127) on primary surgery (n=168) or after neoadjuvant chemotherapy (n=115). 84 patients carried germline mutation in BRCA1 (n=77) or BRCA2 (n=7) genes, while 199 ovarian cancer patients were classified as sporadic. High-grade serous ovarian cancer patients treated with neoadjuvant chemotherapy had a lower disease-free interval compared with those undergoing primary surgery followed by adjuvant therapy (7.8 vs 14.2 months, p<0.001). This difference was attributed mainly to sporadic cases (5.1 vs 12.2 months, p<0.001), while BRCA1 -associated cancers had a similar disease-free interval regardless of the sequence of treatments (12.5 vs 15.8 months, p=0.53). When treated with neoadjuvant chemotherapy, BRCA1 -mutated patients had improved overall survival as compared with sporadic cases (45.7 vs 25.3 months, p=0.007), while patients subjected to primary surgery showed similar overall survival irrespective of BRCA1 status (54.6 vs 53.9 months, p=0.56). A total of 29/61 (48%) BRCA1/2 -associated patients relapsed as a single local tumor; this was lower in sporadic cancer patients (38/134 (28%); p=0.01). Conclusion: In BRCA1 mutation carriers, the oncologic outcomes are similar when comparing primary surgery versus neoadjuvant chemotherapy. In addition, BRCA1 -mutation carriers often have a single site of disease when diagnosed with recurrent ovarian cancer.